2023
DOI: 10.7759/cureus.41721
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practice of Vaccination Among Parents in Jeddah City, Saudi Arabia

Abstract: Background Vaccine misconception plays an important role in delaying vaccination for children, which can lead to serious health problems. Assessing the knowledge, attitude, and practice (KAP) and potential associated factors among Saudi parents of preschool and school-age children and adolescents for all types of vaccines would help increase vaccine coverage. Methodology This cross-sectional, questionnaire-based survey was performed among parents in Jeddah, Saudi Arabia. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…It shows the distribution of caregivers with sufficient knowledge, insufficient knowledge, and those who did not answer questions about child vaccination. This affirms previous conversations [ 47 , 48 ] and emphasises the importance of assessing caregiver knowledge, which can impact vaccination decisions and adherence.…”
Section: Discussionsupporting
confidence: 87%
“…It shows the distribution of caregivers with sufficient knowledge, insufficient knowledge, and those who did not answer questions about child vaccination. This affirms previous conversations [ 47 , 48 ] and emphasises the importance of assessing caregiver knowledge, which can impact vaccination decisions and adherence.…”
Section: Discussionsupporting
confidence: 87%
“…These results align with Alghamdi et al's study in Saudi Arabia, which showed that the majority of parents exhibited positive knowledge, attitudes, and practices regarding vaccination, which were influenced by sociodemographic factors. Nonetheless, addressing vaccination hesitancy by further targeting the identified contributing factors is warranted [18].…”
Section: Discussionmentioning
confidence: 99%